Centrality of Pregnancy and Prenatal Attachment in Pregnant Nulliparous After Recent Elective or Therapeutic Abortion - Smorti, Martina; Ponti, Lucia; Bonassi, Lucia; Cattaneo, Elena; Ionio, Chiara (Frontiers in Psychology, 2020)
Background: there are two types of voluntary interruption of pregnancy: elective and therapeutic abortion. These forms are different for many reasons, and it is reasonable to assume that they can have negative consequences that can last until a subsequent gestation. However, no study has analyzed the psychological experience of gestation after previous abortion, distinguishing the two forms of voluntary interruption of pregnancy. Objective: to explore the level of prenatal attachment and centrality of pregnancy in nulliparous low-risk pregnant women with previous recent (<3 years) elective or therapeutic abortion. Method: 34 nulliparous pregnant women with history of abortion (23 elective and 11 therapeutic abortion) aged from 27 to 48 years (Mean= 37.17) were recruited in the maternity ward of a public hospital of the metropolitan area of Tuscany and Lombardy (Italy) during the 3rd trimester of gestation. Participants filled out a battery of questionnaires aimed at assessing prenatal attachment and centrality of pregnancy. Results: Analyses of variance (ANOVA) showed that women with a history of elective abortion reported higher centrality of pregnancy than women with past therapeutic abortion. On the contrary, women with past therapeutic abortion reported higher prenatal attachment. Conclusions: elective and therapeutic abortion are different experiences that impact the way women experience a subsequent pregnancy. Future research should further investigate the psychological experience of gestation after abortion.